Settlement balances deconstructed - Parnell Chu; Grahame Johnson; Scott Kinnear; Karen McGuinness; Matthew McNeely (Bank of Canada, 2022)
The concept of settlement balances is simple in its definition but complex when attempting to understand how they interplay between a central bank and the financial system. Settlement balances can be defined as interest-bearing deposits that belong to participants of Canada's payment system and that are an integral part of the high-value payment system. In response to the economic shock caused by the COVID-19 pandemic, the Bank of Canada undertook a range of extraordinary policy actions to provide exceptional liquidity to support the economy and ensure a stable and efficient Canadian financial system. The Bank's extraordinary policy actions led to a rapid increase in the Bank's asset holdings, followed by a corresponding increase in liabilities-mostly in the form of settlement balances. In fact, settlement balances grew by more than 1,500 times their pre-pandemic amount. The significant increase in settlement balances has piqued public interest; people want to better understand them. More specifically, people want to explore how settlement balances are created and the Bank's role in that process, and what effects elevated levels can have on the Bank's balance sheet and the financial system more broadly. This paper deconstructs settlement balances into four key concepts. It also provides historical context, explores the current state of settlement balances at the Bank of Canada, explains the factors that will influence their future evolution, and looks at the regulatory impacts of some of the actions taken. This work seeks to broaden the public's understanding of the Bank's role in promoting a safe and stable financial system in Canada.
Keywords: E; E5; E58; E59; E6; G; G0; G01; 330; Central bank research; Coronavirus disease (COVID-19); Financial markets; Monetary policy implementation